THE ASCEND IN DOMESTIC ABUSE AMIDST COVID-19: AN APPRAISAL OF POLICY RESPONSES IN THE LIGHT OF PREVAILING LEGISLATIVE FRAMEWORK (International Journal of Food and Nutritional Sciences, 2022)
COVID-19 hit humanistic perspective of life hard and brought with it multiple series of challenges in the form of health hazards and risks, mental trauma, psychological imbalances and plethora of concealed effects on the society. As the deadly virus spread over newer, remote and distant places, it erased physical spaces for vulnerable sections of the society including women, children and elderly, where in it looked nothing short of a task to cope with the new realities of life. A major setback witnessed in this pandemic situation is the rise of domestic abuse, which has made living conditions for women considerably worse.